Concern regarding H3-subtype avian influenza virus - Yu, Jiantao; Yao, Qiucheng; Liu, Jing; Zhou, Yan; Huo, Miaotong; Ge, Ye (Frontiers in Microbiology, 2023)
The H3-subtype of avian influenza virus (AIV) is one of the most frequently detected low pathogenic avian influenza virus (LPAIV) subtypes in birds and fowls, causing substantial economic loss to the poultry industry. Most importantly, besides poultry, mammals could also be infected with it, such as swines, canines, equines, felines, and humans, posing a serious public health threat. This allows the virus to persist widely in poultry and wild birds for a long time, where it may mix with other subtypes, providing conditions for viral recombination or reassortment. Currently, the monitoring of H3-subtype AIV is inadequate, and there is a lack of effective prevention and control measures for H3-subtype AIV. Here, the epidemiology, phylogeny, and genetic variation of H3-subtype AIV were analysed, and nonsynonymous and synonymous substitution rates (dN/dS) were calculated. Through these steps, we aimed to clarify the current epidemiological feature and evolutionary characteristics of H3subtype AIV, and provide an operative reference for future scientific control of H3subtype AIV.